Women's attributions subsequent to miscarriage : an exploratory study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Kennedy, Fiona Margaret (Massey University, 1993)
Although spontaneous abortion is a routine medical event, no definitive etiology exists, and research available indicates reactions can be problematic. To investigate the relationship of attributions about miscarriage and psychological well-being, a partial replication was conducted of an earlier study. In the present study, forty-eight women were interviewed about their attributions, emotional reactions and their level of information about miscarriage. Madden's (1988) format was used, and a well-being measure was administered. Few women made attributions to themselves or to others. Women were more likely to attribute responsibility to chance. The hypothesised relationships of attributions with psychological well-being, received equivocal support. As hypothesised, respondents generally reported low levels of information about miscarriage, and this was especially pronounced in women without prior experience of miscarriage. These findings are discussed, and suggestions made for future research both on attributions, and perinatal loss. Concluding remarks include observations about miscarriage as a life event, and the practical implications of the research.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology